Investigation of the dynamics of charged particle beams in two-dimensional magnetic prisms with magnetic screens - Sharipov C.У.; Spivak-Lavrov И.Ф. (Recent Contributions to Physics, 2025)
This review article describes analytical expressions for the scalar magnetic potential of a two-dimensional magnetic prism with magnetic screens. The physical and instrumental characteristics of two-dimensional magnetic prisms are calculated using dimensionless Newton’s equations, as well as analytical expressions describing the magnetic field of the prism itself. With this approach, the magnetic field induction is calculated through the gradient of the scalar potential, which makes it possible to accurately determine its distribution at different points in space. The use of dimensionless differential equations to describe the motion of charged particles in electromagnetic fields greatly simplifies the process of numerical calculations, since such equations allow you to get rid of unnecessary parameters and make the results more universal. This, in turn, increases the efficiency of calculations, making them less dependent on specific units of measurement and experimental conditions. As a result of the calculations, data were obtained on the corpuscular-optical properties of two-dimensional magnetic prisms with magnetic screens operating in the telescopic focusing mode, which is important for further research and technology development in this field.